The value result of ankle-brachial index among the lower extremity ulceration diseased patients with artery aetiology - Cwajda-Białasik, Justyna; Mościcka, Paulina; Szewczyk, Maria T.; Jawień, Arkadiusz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2016)
Introduction : It is estimated that the lower extremities asymptomatic ischaemia frequency is 29% approximately, among the population over fifty year old. It was also showed that 18% lower extremities ulceration, which were primary diagnosed as venous, has mixed aetiology, also called arterial-venous. The very simple screening tool which is able to tell the presence of peripheral ischaemia is the ankle- brachial index. The aim of the study was the ankle-brachial index value result and also the presence of mixed aetiology among people having lower extremity ulceration disease. Material and methods : The following studies include 398 diseased patients of Arterial Surgery Clinic and Chronic Wound Healing Clinic with peripheral arteries disease: 252 diseased patients with Chronic Venous Insufficiency (CVI) and 146 patients with Peripheral artery disease (PAD). Ankle-brachial index (ABI) was performed among all diseased people. Results : The average value of ankle- brachial index was different in the compared groups and was characteristically lower among patients with PAD (1.06 vs. 0.73). Among the CVI group, the 10,8% diseased without ulceration and 14.7% with ulceration, the ABI occured to be below and above the norm. The ankle- brachial index dependence on the chosen variables was shown. For instance the presence of diabetes and tobacco smoking and the level of physical activeness and ulceration appearance. Conclusions : Providing the diseased person with an effective but also a safe ulceration therapy, requires a complex diagnose which counts all the causal factors being involved into wound appearance, mainly the presence of asymptomatic PAD and diabetes. Equally the lower value of ankle- brachial index and diabetes coexistence were related to higher risk of an extremity ulceration.